INVESTIGATION OF THE EFFECT OF Fe ON Ni CATALYSTS FOR CARBONATE CONVERSION OF METHANE (Conferencea, 2022)
In this work, an activated Ni catalyst for carbonate conversion of methane was prepared by placing γ-Аl2О3 in solutions of nickel and iron nitrates. The time dependence of methane conversion was studied for different catalysts. In these processes, CО2/CH4=1:1,41 ratio was obtained. As a result of the research conducted, the methane effect of Fe on Ni/Al2O3 catalystfor conversion following possible mechanism was proposed.